PEMBELAJARAN KREATIF BERBASIS MODEL LAGU ANAK DALAM MEWUJUDKAN ANAK BERKARAKTER - Bayu Aji Wicaksono; Indar Sabri; Setyo Yanuartuti; Warih Handayaningrum (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
This study explores the effectiveness of creative learning based on children's song models in developing children's character. Using a literature review approach, this research analyzes the literature on creative learning and character development in children. Findings from the literature review indicate that creative learning based on children's song models has great potential in shaping positive character traits in children. Through this model, children can actively engage in enjoyable learning experiences while internalizing character values embedded in song lyrics. The use of music in learning also enhances children's motivation, creativity, and communication skills. This research makes a significant contribution to understanding and developing innovative teaching methods for children's character development. The importance of fostering good character in children is widely recognized, and this approach based on children's song models offers an effective strategy to achieve this goal. By integrating music and creativity into the learning process, it is hoped that the younger generation can become intellectually sharp and possess positive personalities in their daily lives.